Genetic Characterization of Streptococcus iniae in Diseased Farmed Rainbow Trout (Onchorhynchus mykiss) in Iran - A. Erfanmanesh; M. Soltani; E. Pirali; S. Mohammadian; A. Taherimirghaed (The Scientific World Journal)
Genetic characterization of strains of Streptococcus iniae recovered from morbidity and mortality of farmed rainbow trout in different provinces of Iran were studied. The Gram-positive cocci isolates were obtained from the kidney tissues of diseased rainbow trout on blood agar at 25°C for 72 h. The grown bacteria were then characterized using biochemical and molecular works. The identified 26 isolates of S. iniae producing a 513 bp in PCR procedure were then compared using random amplified polymorphic DNA (RAPD) analysis using 9 random primers. The phylogenetic tree of the RAPD product using UPMGA software included these strains in one genetic group but into two clusters. The results of this study show that S. iniae strains from the diseased rainbow trout in the north part of Iran are genetically similar to those strains in the south and west parts of the country.